Cardiovascular risk factors and incident giant cell arteritis: a population-based cohort study. (4th May 2019) - Tomasson, G; Bjornsson, J; Zhang, Y; Gudnason, V; Merkel, PA
Abstract : Objective : To assess the strength of the effect of cardiovascular risk factors on the incidence of giant cell arteritis (GCA) in a general population context. Method : Data from the Reykjavik Study (RS), a population-based cohort study focusing on cardiovascular disease, were used. Everyone born in 1907–1935 living in Reykjavik, Iceland, or adjacent communities on 1 December 1967 were invited to participate. Subjects attended a study visit in 1967–1996 and information on cardiovascular risk factors [smoking habits, blood pressure, diabetes, body mass index (BMI), and serum cholesterol] was obtained. All temporal artery biopsies obtained from members of the RS cohort were re-examined by a single pathologist with expertise in vascular pathology. Effects of risk factors on GCA occurrence are expressed as incidence rate ratios (IRRs) with 95% confidence intervals (CIs). Results : Altogether, 19 241 subjects contributed a median of 23.1 (interquartile range 17.6–29.4) years after the age of 50 to this analysis. During 444 126 person-years of follow-up, 194 subjects developed GCA, corresponding to an incidence rate of 43.6 (95% CI 37.8–50.2) per 100 000 person-years. Being overweight or obese  were inversely associated with GCA, especially in women [IRRs 0.70 (0.48–1.02) and 0.31 (0.14–0.71), respectively]. There was a weaker association between BMI and incident GCA in men. Smoking was inversely associated with GCA in men [IRR 0.47 (0.27–0.81)], but not in women. Conclusions : The incidence of GCA in Iceland is very high. High BMI protects against the occurrence of GCA, and smoking may protect against GCA in men.